An Islamic Boarding Schools As Means Of Regeneration In The Development Of Da'wah - Mahmud Fauzi Suali (Yayasan Ilomata, 2020)
Islamic boarding schools as a means of regeneration in the development of da'wah. Islamic boarding school is an educational institution that transforms the value of education and example every second and minute and every time from a kyai to his students. Researchers are interested in choosing this topic because no one has conducted research with the same title. It is hoped that the benefits of the research will be of assistance to the pesantren pindok caregivers as well as for prospective da'i who wish to further deepen various dakwah sciences. The reason other researchers are not interested in this title is that they consider Islamic boarding schools as a means of regeneration in the development of da'wah to be ineffective and not optimal. Apart from this research, the writer tries to find a formula for what is done by the Islamic boarding schools to regenerate candidates and those who have become da'i, forged to become qualified da'i. This research was conducted using field research (field research) and qualitative analysis. Therefore, the data collected in this study is in the form of information in the form of descriptions. Qualitative analysis is considered more appropriate in this study, because this analysis is expected to make it more possible to develop this research in order to gain a deeper understanding. Research findings of Islamic boarding schools have a function as a da'wah institution, have elements and systems that are ideal in producing da'i cadres who have broad knowledge and character. Conclusion of the study, Islamic boarding school as a means of regeneration that prepares the next generation of Islam, through the provision of knowledge (leadership, management and insight) in stages and careful planning. The implication of this research is that the cadre model in the development of da'wah in Islamic boarding schools which is deliberately designed in such a way, it is certain that the da'i cadres can develop the knowledge they have and are ready to preach Islamic values ​​wherever they are.